In-depth characterization of phytase-producing plant growth promotion bacteria isolated in alpine grassland of Qinghai-Tibetan Plateau - Li, Qi; Yang, Xiaolei; Li, Jianhong; Li, Mingyuan; Li, Changning; Yao, Tuo (Frontiers in Microbiology, 2023)
The use of plant growth promoting bacteria (PGPB) express phytase (myo-inositol hexakisphosphate phosphohydrolase) capable of hydrolyzing inositol phosphate in soil was a sustainable approach to supply available phosphorus (P) to plants. A total of 73 bacterial isolates with extracellular phytase activity were selected from seven dominant grass species rhizosphere in alpine grassland of Qinghai-Tibetan Plateau. Then, the plant growth promoting (PGP) traits of candidate bacteria were screened by qualitative and quantitative methods, including organic/inorganic Phosphorus solubilization (P. solubilization), plant hormones (PHs) production, nitrogen fixation, 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity and antimicrobial activity. Further experiment were conducted to test their growth promoting effect on Lolium perenne L. under P-limitation. Our results indicated that these bacteria as members of phyla Proteobacteria (90.41%) and Actinobacteria (9.59%) were related to 16 different genera. The isolates of Pseudomonas species showed the highest isolates number (36) and average values of phytase activity (0.267 ± 0.012 U mL–1), and showed a multiple of PGP traits, which was a great candidate for PGPBs. In addition, six strains were positive in phytase gene (β-propeller phytase, bpp) amplification, which significantly increased the shoot length, shoot/root fresh weight, root average diameter and root system phytase activity of Lolium perenne L. under P-limitation, and the expression of phytase gene (bppP) in root system were verified by qPCR. Finally, the PHY101 gene encoding phytase from Pseudomonas mandelii GS10-1 was cloned, sequenced, and recombinantly expressed in Escherichia coli. Biochemical characterization demonstrated that the recombinant phytase PHY101 revealed the highest activity at pH 6 and 40°C temperature. In particular, more than 60% of activity was retained at a low temperature of 15°C. This study demonstrates the opportunity for commercialization of the phytase-producing PGPB to developing localized microbial inoculants and engineering rhizobacteria for sustainable use in alpine grasslands.